5 - REALIDADES OSCILANTES: OBSERVAÇÕES SOBRE O PERFORMATIVO NO TEATRO CONTEMPORÂNEO - Wagner-Lippok, Frithwin; de Oliveira, Tradução de Heidrun Friedel Krieger Olinto; Simoni, Mariana Maia (O Percevejo Online, 2011)
No contexto de um projeto teatral teórico-prático, o autor investigou a função estética e o significado social de “performatividade” em alguns experimentos teatrais contemporâneos. Usando exemplos de encenações “pós-dramáticas”, estratégias de apresentação e extratos de entrevistas, o conceito de “performatividade” é desenvolvido como uma paradoxal estrutura de papéis, e a relação específica entre ator e público é ilustrada pelo paradigma estrutural da “fita de Möbius”: a ambiguidade de suas posições desconstrói a hierarquia dos papéis sociais daqueles que estão presentes, produzindo o evento teatral. A transgressão de limites da representação no sentido da apresentação e da auto-apresentação leva, em diferentes medidas, a combinações criativas de ficção e realidade e a uma mudança na atitude de recepção. Palavras-chave | performatividade | teatro pós-dramático | realidade | ficção | autenticidade FRITHWIN WAGNER-LIPPOK é diretor de teatro, formado no Drama Department da Brock University, em Ontario (Canadá). Fundou o Theater Tantalus em Freiburg, Alemanha (1990), onde dirigiu todas as peças. Foi assistente, entre outros, de Jürgen Kruse e Wolfram Mehring. Diretor e Dramaturgo na Freie Kammerspiele Köln (1997-2000). Assistente de direção no Staatstheater Kassel (2000-2001). Seu primeiro projeto “pós-dramático” de teatro catalão-germânico foi Einsamkeit Solitud 2000, adaptando Na solidão dos campos de algodão, de Bernard-Marie Koltès. A partir de 2000, manteve colaboração regular com Christina Schmutz, com quem produziu e encenou, entre outros, Peix per Peix, de Roland Schimmelpfennig; Deu és un DJ, de Falk Richter; Nomades, de Ulrike Syha e, em 2010, la festa.el foc.la ciutat, de Anja Hilling. In the context of a theoretical-practical theatre project, the author investigated the aesthetic function and social meaning of “performativity” in a few contemporary theatre experiments. Using examples from “post dramatic” theatre shows, presentation strategies and excerpts of interviews, the concept of “performativity” is elaborated as a paradoxical structure of roles. The specific relation between actor and audience it entails is illustrated through the structural paradigm of the Möbius loop: the ambiguity of their positions dismantles the hierarchy of social roles of those present who, together, bring forth the theatrical event and in doing so lose any individual authority over it. The transgression of the limits of representation towards presentation and self-presentation leads, in variable proportions, to creative combinations of fiction and reality, and thereby to a change in how the work is received by the public. Keywords | performativity | post dramatic theatre | reality | fiction | authenticity FRITHWIN WAGNER-LIPPOK was trained as an actor and director at the Drama Department of the Brock University, Ontario (Canada). He founded the Theater Tantalus in Freiburg (1990), where he directed all the plays. He worked as an assistant with Jürgen Kruse and Wolfram Mehring. He was appointed director and dramaturge of the Freie Kammerspiele Köln between 1997 and 2000 and was assistant director in Staatstheater Kassel 2000-2001. He realized the first catalan-german “post-dramatic” theatre project: Einsamkeit Solitud 2000 adapting En la solitut dels camps de cotó by Koltès. Since the year 2000, he is a regular collaborator of Christina Schmutz, with whom he staged, among others: Peix per Peix by Roland Schimmelpfennig; Deu és un DJ by Falk Richter; Nomades by Ulrike Syha (International Theatre Festival of Sitges); no dormim by Kathrin Röggla, and in 2010, la festa.el foc.la citutat, by Anja Hilling.